Salutogenic health promotion program for migrant women at risk of social exclusion - A. Bonmatí-Tomas; M. C. Malagón-Aguilera; S. Gelabert-Vilella; C. Bosch-Farré; L. Vaandrager; M. M. García-Gil; D. Juvinyà-Canal (International Journal for Equity in Health, 2019)
Abstract Background Migrant women at risk of social exclusion often experience health inequities based on gender, country of origin or socioeconomic status. Traditional health promotion programs designed for this population have focused on covering their basic needs or modifying lifestyle behaviors. The salutogenic model of health could offer a new perspective enabling health promotion programs to reduce the impact of health inequities. This study evaluated the effectiveness of a salutogenic health promotion program focused on the empowerment of migrant women at risk of social exclusion. Methods A four-session salutogenic health promotion program was conducted over a period of 6 months. In a quasi-experimental pre-test post-test design, an ad hoc questionnaire was administered to 26 women to collect sociodemographic data, together with 5 validated instruments: Antonovsky’s Sense of Coherence (SOC-13), Duke-UNC-11 (perceived social support), Quality of Life Short Form-36 (SF-36), Rosenberg’s Self-Esteem Scale, and the Cohen et al. Perceived Stress Scale (PSS-10). Descriptive analysis and multiple linear regression models were performed. Statistical tests were considered significant with a two-tailed p value < 0.05. Results Participants had a low initial SOC-13 score (60.36; SD 8.16), which did not show significant change after the health promotion program. Perceived social support (37.07; SD 6.28) and mental quality of life also remained unchanged, while physical quality of life increased from 50.84 (SD 4.60) to 53.08 (SD 5.31) (p = 0.049). Self-esteem showed an increasing trend from 30.14 (SD 4.21) to 31.92 (SD 4.38) (p = 0.120). Perceived stress decreased from 20.57 (SD 2.91) to 18.38 (SD 3.78) (p = 0.016). A greater effect was observed at the end of the program in women with lower initial scores for SOC-13 and quality of life and higher initial scores of perceived stress. Conclusions The health promotion program reduced perceived stress, increased physical quality of life and showed a trend toward increased self-esteem, especially among migrant women with multiple vulnerability factors. The salutogenic model of health should be considered as a good practice to apply in health promotion programs and to be included in national policies to reduce health inequity in migrant populations.